Study Of Surgical Site Infections And Antibiotic Susceptibility Pattern Of Isolates At A Tertiary Care Hospital In Kishanganj, Bihar, India (Journal of Pharmaceutical Negative Results, 2023)
Objectives: This present study was to evaluate the surgical site infections and antibiotic susceptibility pattern of isolates at a tertiary care hospital in Kishanganj, Bihar, India. Methods: Pus swabs/specimens were collected from infected surgical sites. All the specimens were inoculated onto blood and MacConkey’s agar within two hours of collection. The agar plates were incubated at 37°C aerobically and were examined for the presence of any growth after 24 hours. Those plates showing no growth were incubated for another 24 hours. The isolates were identified by colonial morphology, Gram’s stain and conventional biochemical tests. Antibiotic susceptibility pattern of the isolates was studied using Kirby Bauer method. Mueller Hinton agar (Difco) was used for antibiotic susceptibility testing. Results: Seventy-five organisms were isolated from the 100 specimens processed. 49 specimens yielded growth of single organism while two isolates were present in rest of the thirteen cases. The most common pathogen isolate was, Staphylococcus aureus (50.67%), followed by Pseudomonas aeruginosa (18.66%), Escherichia coli (12%), Klebsiella pneumoniea (6.66%), Acinetobacter baumannii (4%), and (2.66%) Streptococcus pyogenes, Citrobacter diversus, and Proteus mirabilis including miscellaneous gram negative rods. Conclusions: Staphylococcus aureus is the most common pathogens isolates from Surgical site infections. Hundred percent susceptibility of vancomycin is seen for Staphylococcus aureus and Streptococcus pyogenes. Cephalexin is also hundred percent susceptible for Streptococcus pyogenes. Imipenem, sulbactum ceftriaxone, ceftriaxone and piperacillin – tazobactum are more susceptible for gram negative rods.